Data and Materials: Summarizing Global SARS-CoV-2 Geographical Spread by Phylogenetic Multitype Branching Models - Kiang, Hao Chi (Linköping University, 2022)
Raw numerical results, phylogeny, and related data for the conference proceeding article "Summarizing Global SARS-CoV-2 Geographical Spread by Phylogenetic Multitype Branching Models".

To merge these files in Unix shell, simply use the "cat" command to concatenate the four parts into a single big "tar.gz" file, then decompress as usual. For example: "cat DATASET01.tar.gz DATASET02.tar.gz DATASET03.tar.gz DATASET04.tar.gz > FULL.tar.gz". Then decompress the newly generated FULL.tar.gz.

On Windows, rename "DATASET0X.tar.gz" to "DATASET.tar.gz.00X" for each X={1,2,3,4}. Then use the "7-Zip" app to open the part 1 (i.e., "DATASET.tar.gz.001"); then 7-Zip should automatically detect the presence of part 2~4 and decompress everything.

The dataset was originally published in DiVA and moved to SND in 2024.
Data and Materials: Summarizing Global SARS-CoV-2 Geographical Spread by Phylogenetic Multitype Branching Models
Keywords: coronaviruses; coronavirus; phylogenetics; fylogenetik; SARS-CoV-2 virus; SARS-CoV-2-virus; Bioinformatics and Computational Biology; Bioinformatik och beräkningsbiologi